Jewish Messiahs in a Christian Empire: A History of the Book of Zerubbabel - Himmelfarb, Martha (Harvard University Press, 2017)
Cover -- Title Page -- Copyright -- Dedication -- Contents -- Introduction -- 1. Text and Context -- 2. The Mother of the Messiah -- 3. The Messiah Son of David and the Suffering Servant -- 4. The Servant-Messiah beyond Sefer Zerubbabel -- 5. The Dying Messiah Son of Joseph -- 6. Sefer Zerubbabel after Islam -- Conclusion -- Appendix: Translation of Sefer Zerubbabel according to the Sefer Hazikhronot Manuscript -- Notes -- Acknowledgments -- Index